2018
DOI: 10.1186/s12882-017-0798-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in sugarcane workers in Cameroon: a cross-sectional study

Abstract: BackgroundAgricultural workers especially in sugarcane plantations have a high risk of chronic kidney disease (CKD). Little is known about CKD among sugarcane plantation workers in Cameroon. This study sought to evaluate the prevalence and identify factors associated with CKD in sugarcane plantation workers in Cameroon.MethodsWe conducted an analytic cross-sectional study including 204 adult workers at the sugarcane plantation complex in Mbandjock, Cameroon; over 500 m above sea level. Chronic kidney disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
(29 reference statements)
0
14
0
1
Order By: Relevance
“…The prevalence of CKD among sugarcane plantation workers was 3.4% [26]. The prevalence of CKD among rst-degree family relatives of persons living with CKD on hemodialysis was 15.9% [29].…”
Section: Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of CKD among sugarcane plantation workers was 3.4% [26]. The prevalence of CKD among rst-degree family relatives of persons living with CKD on hemodialysis was 15.9% [29].…”
Section: Searchmentioning
confidence: 99%
“…Search terms #1 "Kidney disease*" OR "kidney failure" OR "Renal disease" OR "Renal insu ciency" OR "Chronic kidney" OR "Chronic renal" OR "CKD" OR "CKF" OR "CRD" OR "end-stage renal" OR "end-stage kidney" OR "endstage renal" OR "endstage kidney" OR "uremia" OR "uraemia" OR "dialysis" OR "hemo ltration" OR "haemo ltration" OR "hemodia ltration" OR "haemodia ltration" OR "hemodialysis" OR "haemodialysis" OR "renal dialysis" Prevalence of CKD in Cameroon Table 2 summarizes the studies that reported on the prevalence of CKD in Cameroon. The prevalence of CKD was reported in 11 studies in Cameroon [11,17,[24][25][26][27][28][29][30][31][32]. All studies were cross-sectional studies, 4 (36.4%) were community-based, and 2 (18.2%) were conducted in rural areas.…”
Section: Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic kidney disease (CKD), which mainly arises from hypertension, diabetes mellitus and chronic glomerulonephritis, has attracted growing attention in recent years because it affects up to 13.4% of the population worldwide [1]. CKD can be defined as kidney dysfunction characterized by fibrillar collagen deposition lasting for at least 3 months [2,3].…”
Section: Introductionmentioning
confidence: 99%